1974
DOI: 10.1111/j.1365-2222.1974.tb01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgE determination by RAST compared with skin and provocation tests in allergy diagnosis with birch pollen, timothy pollen and dog epithelium allergens

Abstract: Summary In sixty‐five patients with asthma or allergic rhinitis, intracutaneous tests and provocation tests were performed with birch pollen, timothy pollen and/or dog epithelium allergen. The clinical diagnosis was compared with RAST results obtained with identical allergen preparations for in vivo as well as in vitro testing in two different laboratories. An overall correlation between in vitro and in vivo diagnosis was found in 85% of the cases. It is suggested that a scoring system using the sum of case hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

1976
1976
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 6 publications
(9 reference statements)
4
24
1
1
Order By: Relevance
“…35 patients had negative reactions to all allergens used. 34 patients had earlier been sub jected to immunotherapy but our previous study did not indicate any significant influence on the results [5].…”
Section: Patientsmentioning
confidence: 96%
See 2 more Smart Citations
“…35 patients had negative reactions to all allergens used. 34 patients had earlier been sub jected to immunotherapy but our previous study did not indicate any significant influence on the results [5].…”
Section: Patientsmentioning
confidence: 96%
“…Economical considerations have also to be included before the RAST can be more generally recommended to replace the conventional biologic test methods in the elaboration of a complicated allergy diagno sis. In a previous study we suggested that combinations of RAST results and the patients' case histories in a score system could be used for screening allergic patients, thus making provocation tests necessary only in a limited number of cases [5]. The results of applying this approach to the pre sent patient material will be discussed in a further paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten patients (age range 22-58 years) with exogenous seasonal asthma were investigated, Manifest exogenous atopic allergic asthma was considered when the sum score for history of positive symptomatology (max score 3), SPT (max score 3) and positive RAST titres (max score 3) was at least 5 (2). At the time of blood sampling, all patients had been free from all drugs, including oral contraceptives, for at least 10 days.…”
Section: Blood Donorsmentioning
confidence: 99%
“…In order to make use of the quantitative information available from the ST and the RAST results as well as to some extent from the CH, a scoring system suggested in a previous paper [4] was employed in the present investigation. It was found that when two diagnostic methods were used to gether, a 100% agreement with PT could be obtained in cases with maximal scores (scores of 6).…”
Section: Discussionmentioning
confidence: 99%